SIRRI MARRIAGE FROM THE PERSPECTIVE OF ISLAMIC LEGAL PHILOSOPHY - Suryani, Suryani (IBLAM LAW REVIEW, 2022)
This research aims to describe the study of Islamic legal philosophy regarding unregistered marriages, with the problem of how to carry out unregistered marriages, the factors that influence them, and how Siri marriages are according to the review of Islamic legal philosophy, to describe the implementation of unregistered marriages and the factors that influence them, as well as analysis of Islamic legal philosophy on the implementation of unregistered marriage laws. This research is library research with sources from literature that talk about unregistered marriages and Islamic legal philosophy. Research shows that the factors that influence unregistered marriages are religious factors, not having the approval of parents, economics, muamalat, infidelity, and polygamy. From a juridical perspective, a review of Islamic philosophy states that the legality of a marriage is as stated in Article 2 paragraph (2) of Law No. 1 of 1974 concerning marriage, that every marriage is registered according to the applicable laws and regulations. In the compilation of Islamic Law, article 5 paragraph 10 also requires that every marriage that takes place be recorded to ensure marital order for the community. Based on the study of ushul fiqh, registration of marriages or marriages, apart from guaranteeing legal certainty for husband and wife couples, it is also necessary to pay attention to the Maqashidu Syari'ah aspect (purpose of law) in Islam, namely that marriages or marriages that are not registered will cause a lot of harm or harm to husband and wife couples. the results of the marriage as well as for parties related to the marriage.